Amplification of human papillomavirus early genes for detection of nine genotypes in Venezuelan women. - Michelli, Elvia; Téllez, Luis; Mendoza, José; Noguera, María; Milano, Melisse; Vera, Reauben; Callejas, Diana (Investigación Clínica, 2015)
Genotyping of human papillomavirus (HPV) by molecular methods may enhance assessment information for screening and following of cervical infection. In this study, cervical samples were obtained from 250 women, along with colposcopic and cytological evaluations. A Nested-PCR-Multiplex assay was used for HPV detection and genotyping for HPV E6/E7 early regions. Infection with HPV was detected in 26.0% of the samples, with 98.46% positive for at least one genotype. High-risk HPVs were identified in 98.44%. HPV18 infection was detected in 76.92% of samples and HPV16 in 36.92%, whether as individual or as multiple infections. These infections were seen more frequently in women under 35 years of age (64.7%). The Pap-smear examination showed that 16.92% (11/65) of the samples had cervical changes suggesting HPV infection, whereas the colposcopic evaluation was suggestive of HPV infection in 47.69% (31/65) of DNA-HPV positive samples. There was a high frequency of high-risk HPV genotypes, particularly HPV18, alone or in multiple-type infections. Colposcopy findings showed to have a high predictive value for the diagnosis of HPV infection. The results reflect that over 50% of HPV-positive patients had a normal colposcopy and/or cytology, highlighting the importance of including HPV testing along with genotype identification in routine gynecological evaluations.